System of Inclusive Methodological Work for the Diagnosis of University Student’s Admission (International Journal of Psychosocial Rehabilitation, 2020)
The research was structured considering the application of theoretical methods as initial elements and empirical methods in their subsequent application, elements that contrasted the information obtained to arrive at reliable results. In the first instance of the research report, it is devoted to the analysis of the orientation process of university teachers and the diagnosis of the level of higher education and to the diagnosis of the current situation of the research problem. In the second instance, the argumentation of the methodological conception is presented, and the methodological work system is based on it. Finally, the evaluation of the feasibility of the proposal is specified. All research work was carried out with a representative sample of teachers and students from the five universities that exist in the province of Manabí, Republic of Ecuador, and three higher technological institutes of the same province. All this work was done during the 2014-2018 period.